The Interannual Variability of the Fall Size of Young-of-The-Year Chub (Squalius cephalus): Influence of Phenology, Growth Patterns and Abiotic Factors - Logez, Maxime; Bounket, Bernadette; Gibert, Pierre; Carrel, Georges; Diouloufet, Virginie; Colombet, Xavier; Morat, Fabien (Frontiers in Environmental Science, 2021)
Long-term surveys confirms the rapidity of environmental and biological changes undergone by endangered species but that also concerned relatively ‘tolerant’ species, especially common rheophilic species such as European Chub (Squalius cephalus, Linneaus 1758). As many organisms, fish are highly vulnerable during their first life stages. Body size is a determinant factor for ecosystem functioning and for fish to survive to predators or to winter conditions. While numerous studies has already demonstrated the large variability of autumnal size of fish hatched during the year, few have focused on the factors explaining these interannual variations and on the growth patterns underlying these distributions. Using otoliths of young-of-the-year (YOY), we studied how the interannual variability in fall sizes of chubs might be related to varying phenology, temperature, hydrology and growth patterns. YOY were sampled in three sections of the same reach of the Rhône River with contrasted hydrological regime: an artificial deep lotic channel (the tailrace of Bollène), a bypassed section with both lotic and lentic areas (former river channel before dam construction) and a reservoir with lentic deep waters. Sampling was performed on each sector during two thermally distinct years. Temperature had an important effect on both phenology and growth rate but it was not expressed similarly among river sections. Fish hatched earlier in the warmer year. Fish sizes were positively correlated with growing degree-days, but with distinct relationships between years and sections. The growth was faster in the warmer year, and in the warmer section, but differences in growth patterns varied between sections. In the bypassed section, the difference was slight, almost not significant, even if temperatures were very different between the two years considered. Autumnal variations in size could be explained either by an earlier phenology or by a faster growth due to higher temperatures occurring during the final part of the growing period. Our results were in accordance with general theory's predictions relating individual growth to temperature, but they also showed that other factors might mitigate the influence of temperature on fish early life stages.